Córdoba, Spanien: Die Arbeiten der Jahre 2013 und 2014 - Arnold, Felix (e-Forschungsberichte des DAI, 2023)
The Islamic country estate of ar-Rummānīya is located in the foothills of the Sierra Morena, some 10 km west of the city of Córdoba (Spain). The estate was erected in 965 CE by ad-Durrī “the Little”, a finance minister of the caliph al-Hakam II. The building complex encompasses four terraces, three of which were designed as gardens. On the uppermost terrace stood a series of palatial buildings, including two halls and a large water basin. The aim of the last two seasons of excavation has been the investigation of the garden. Detailed information was gained on the irrigation system and the kinds of plants that grew here. Botanical studies provide evidence for the presence of olive trees, almonds, pomegranate, vine, myrtle and lavender as well as a range of herbs and flowers.